Application of Soft Grippers in the Field of Agricultural Harvesting: A Review - Daode Zhang; Wei Zhang; Hualin Yang; Haibing Yang (Machines)
This review summarizes the important properties required for applying soft grippers to agricultural harvesting, focusing on their actuation methods and structural types. The purpose of the review is to address the challenges of limited load capacity and stiffness, which significantly hinder the broader application of soft grippers in agriculture. This paper examines the research progress on variable stiffness methods for soft grippers over the past five years. We categorize various variable stiffness techniques and analyze their advantages and disadvantages in enhancing load capacity, stiffness, dexterity, degree of integration, responsiveness, and energy consumption of soft grippers. The applicability and limitations of these techniques in the context of agricultural harvesting are also discussed. This paper concludes that combined material variable stiffness technology with a motor actuation claw structure in soft grippers is better suited for agricultural harvesting operations of woody crops (e.g., apples, citrus) and herbaceous crops (e.g., tomatoes, cucumbers) in unstructured environments.